The grammatical lesson in Ibn Muʿṭī’s Alfiyya – an approach close to modernity and enduring foundations - laouidji, ammar; si Abdallah, Fatima Zahra (El Omda in Linguistics and Discourse Analysis, 2025)
Ibn Muʿṭī al-Zawāwī al-Bijāʾī is considered one of the Algerian linguists whose rich scholarly contribution and significant impact on language and grammar have been acknowledged by history. This is due to the works and commentaries he produced across various fields, aimed at facilitating knowledge-seeking for students and encouraging them to benefit and expand their learning, relying on clear and accessible language. Accordingly, this study aims to demonstrate Ibn Muʿṭī’s mastery in composing his Alfiyya, as he guided young learners by engaging their intellectual capacities and cognitive abilities, enabling them to grow into grammatical understanding and acquire linguistic intuition. It also highlights the conscious methodology he adopted in presenting its content, making it a reliable source for students and researchers today.